Upregulated influenza A viral entry factors and enhanced interferon-alpha response in the nasal epithelium of pregnant rats. Issue 5 (May 2022) - Giri, Tusar; Panda, Santosh; Kelly, Jeannie C.; Pancaro, Carlo; Palanisamy, Arvind
Abstract: Despite the increased severity of influenza A infection in pregnancy, knowledge about the expression of cell entry factors for influenza A virus (IAV) and the innate immune response in the nasal epithelium, the primary portal of viral entry, is limited. Here, we compared the expression of IAV cell entry factors and the status of the innate immune response in the nasal epithelium of pregnant vs . non-pregnant female rats. IAV cell entry factors — sialic acid [SA] α-2, 3- and α-2, 6-linked glycans for avian and human IAV, respectively — were detected and quantified with lectin-based immunoblotting and flow cytometry. Baseline frequencies of innate immune cell phenotypes in single cell suspensions of the nasal epithelium were studied with flow cytometry. Subsequently, the magnitude of interferon and cytokine responses was studied with ELISA and cytokine arrays after intranasal resiquimod, a Toll-like receptor 7/8 agonist that mimics IAV infection. We noted substantially increased expression of cell entry factors for both avian and human IAV in the nasal epithelium during pregnancy. Assessment of the innate immune state of the nasal epithelium during pregnancy revealed two previously unreported features: (i) increased presence of tissue-resident plasmacytoid dendritic cells, and (ii) markedly enhanced release of interferon-α but not of the other interferons or cytokines 2 h after intranasal resiquimod. Collectively, our findings challenge the conventional notion of pregnancy-induced immunosuppression as a cause for severe influenza A disease and suggest the need for focused studies on viral tropism during pregnancy to better understand the proximate cause for the observed immunopathology. Abstract : Influenza A; Host-pathogen interaction; Nasal epithelium; Pregnancy; TLR7; pDC.